Unlocking Pakistan’s Debt Conundrum: A Deep Dive into the Dynamics of Debt Servicing and External Debt Stock - Shabeer, Muhammad Ghulam; Azra, Ms.; Anwar, Ayesha; Zubair, Rabia (Journal of Economic Impact, 2024)
Pakistan stands at a crossroads where the burgeoning debt servicing cost of Rs 7.3 trillion is going to swallow the lion’s share of the projected revenue of Rs 9.2 trillion. This revenue also includes the Rs 5.2 trillion share allocated to the provinces. It is essential to study the causes of such a high debt stock rate, which requires a large outflow of foreign reserves. This study took 50 years of data about Pakistan and analyzed certain determinants of debt stock including debt service cost, budget deficit, military expenditure, import bill, and population. ARDL was used after finding a mixed order for stationery. The short and long-run analysis is undertaken. The Result shows that debt cost has a significant negative impact on debt stock, whereas budget deficit, military expenditure, import, and population have a significant positive impact on national debt. Based on the results, this study suggests that military expenditure and imports should be decreased to control national debt. The population must be maintained at an optimal level. The government should not go for a budget deficit as it requires further loans. The Results were checked for robustness and the model was stable.